2009
DOI: 10.5747/cv.2009.v01.n1.v011
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação Do Limiar Auditivo Em Profissionais De Odontologia

Abstract: A perda auditiva induzida pelo ruído (PAIR) é uma das doenças do trabalho mais comuns em nosso meio. Os profissionais de odontologia trabalham em ambientes com alto nível de ruído, portanto, são passíveis de apresentarem PAIR. Dessa forma, o objetivo deste estudo foi avaliar os limiares auditivos por meio da audiometria tonal liminar (ATL) em profissionais de Odontologia. A população deste estudo foi composta por um total de 30 cirurgiões-dentistas que atuam há mais de três anos na profissão, com idade máxima … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
2
1
1
Order By: Relevance
“…Other studies with dentists in Brazil were found also sensorioneural hearing losses, but in greater percentage than this, such as study in Paraná, with 85 surgeon dentists, were found 43,5% with hearing changes (9); in a study at Ribeirão Preto/SP (15) with 40 dentists of both genders, all of them with more than five years in profession, occurred 70% of hearing losses; and at Goiás, study with 228 dentists were found 31,58% with suggestive hearing changes of PAIR (16). In the research performed with 30 surgeon dentists in both of genders, it was found 17% of hearing changes in high frequencies (3 and/or 4 and/or 6kHz), lower percentage than this study (10). And, in a study performed in Belgium, the authors found hearing changes of 19,6% of dentists, especially in masculine gender (6).…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…Other studies with dentists in Brazil were found also sensorioneural hearing losses, but in greater percentage than this, such as study in Paraná, with 85 surgeon dentists, were found 43,5% with hearing changes (9); in a study at Ribeirão Preto/SP (15) with 40 dentists of both genders, all of them with more than five years in profession, occurred 70% of hearing losses; and at Goiás, study with 228 dentists were found 31,58% with suggestive hearing changes of PAIR (16). In the research performed with 30 surgeon dentists in both of genders, it was found 17% of hearing changes in high frequencies (3 and/or 4 and/or 6kHz), lower percentage than this study (10). And, in a study performed in Belgium, the authors found hearing changes of 19,6% of dentists, especially in masculine gender (6).…”
Section: Discussioncontrasting
confidence: 65%
“…In the Norm 17 -NR17 (3), which is based on Brazilian Norm -NBR n. 10152 4, it is established that for purposes of acoustic comfort, the maximum level of noise in dental offices must be of 45dBA to 50dBA. Research showed that clinic, the offices and dental laboratories presented high sound pressure levels which lead, in time, impairments to the health of the professionals who work there, like as PAIR among others (5)(6)(7)(8)(9)(10). Study in Brazil found high level pressure of sound in the odontological equipments from a brand largely used, namely: in high rotation 65 to 78,6 dBA, in the amalgam 65,8 to 68 dBA, in sucker of high-power 68,8 a 72 dBA, in ultrasound for cleaning teeth 75,8 to 88 dBA and in the low speed engine 69,8 to 72 dBA (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sabendo que os consultórios e clínicas odontológicas apresentam elevados níveis de pressão sonora, os profissionais podem, com o tempo, apresentar comprometimentos na saúde auditiva (GONÇALVES et. al., 2010); (LELO et. al., 2009).…”
Section: Introductionunclassified